Secondary Stage Education in India An Analytical Overview - Singh, Virendra Pratap (JOURNAL OF INDIAN EDUCATION, 2013)
The present study has analytically overviewed the secondary stage education based on the recent past educational surveys. It provides tangible comparisons pertaining to secondary stage education on the schooling facilities in rural areas, schooling facilities in habitations predominantly populated by scheduled castes and scheduled tribes, schooling facilities in villages, secondary schools, secondary sections in the schools, enrolment in Classes IX and X, science laboratories and computer education, guidance services, pre-vocational courses, secondary stage in oriental schools following general system of education, schools admitting children with disabilities and enrolment taking place in India. The study utilises secondary data collected during recent successive two surveys, namely, sixth and seventh on school education conducted by the National Council of Educational Research and Training under administrative and financial control of the Government of India.